Advances in Computer Graphics : 37th Computer Graphics International Conference, CGI 2020 Geneva, Switzerland, October 20-23, 2020 proceedings - Magnenat, Thalmann Nadia 1946- (Lecture notes in computer science / editors Gerhard Goos, Juris Hartmanis ;, 2020)
This book constitutes the refereed proceedings of the 37th Computer Graphics International Conference, CGI 2020, held in Geneva, Switzerland, in October 2020. The conference was held virtually. The 43 full papers presented together with 3 short papers were carefully reviewed and selected from 189 submissions. The papers address topics such as: virtual reality; rendering and textures; augmented and mixed reality; video processing; image processing; fluid simulation and control; meshes and topology; visual simulation and aesthetics; human computer interaction; computer animation; geometric computing; robotics and vision; scientific visualization; and machine learning for graphics.